World cinema diary of a day : a celebration of the centenary of cinema in conjunction with bfi - Cowie, Peter (Mitchell Beazley, 1994)
"Since the Lumiere Brothers exhibited the first film in Paris one hundred years ago, film has evolved into a major cultural and entertainment force throughout the world. To mark this anniversary, the British Film Institute asked over 1000 filmmakers and other industry players from every continent to record a diary about the work they were doing on one day - June 10, 1993. The result is a unique document that is arguably the most complete look at the international film industry ever assembled, providing a behind-the-scenes look at the sometimes glamorous, oftentimes arduous, always fascinating process of filmmaking." "Never before has there been such in-depth documentation of all aspects of film production, from the first germ of a film idea to the screening of the finished production. World Cinema is filled with accounts of story conferences and budget meetings, casting sessions and set construction, location scouting and costume design. Not only does it cover shooting on the set, but also what happens afterwards, including editing, the laying of sound tracks, distribution, publicity and marketing." "World Cinema is the ultimate collaborative project, with over 1,000 participants and many honorary patrons, including Michael Apted, John Boorman, David Cronenberg, Chen Kaige, Martin Scorsese, Louis Malle, Penelope Spheeris, Bernard Tavernier and Wim Wenders. The contributors include directors, producers, screen-writers, studio executives, agents, actors, cinematographers, sound technicians, special effects artists, stunt men and women, make-up artists, costume designers, film editors, casting directors, composers, distributors, exhibitors, production designers, critics and many others. Inevitably, diarists were working on a wide variety of movies, including blockbusters, standard studio productions, independent films, art house movies, special effects spectaculars and documentaries. Supported by a profusion of photographs and illustrations, this fascinating book is unrivaled as a vital resource on the international film industry today."--Book jacket.